Contribution to the embryology of Leiothrix fluitans (Eriocaulaceae : Poales) - Coan, Alessandra Ike; Rosa, Michele Marcelino; Scatena, Vera Lucia (Elsevier B.V., 2007)
This paper presents a contribution to the understanding of the embryology, especially microsporogenesis, the antipodal cell behavior, and the early stages of the micropylar seed operculum, in Leiothrix fluitans, to elucidate these aspects both within the subgenus Rheocaulon and within the genus in Eriocaulaceae. Contrarily to previous descriptions of this same species, our results show the following: microsporogenesis is of the successive type and results in isobilateral microspore tetrads; the antipodal cells gradually fuse together to form a conspicuous cyst; and the inner integument, which does not develop into an endothelium, shows evidence of the initiation of the seed operculum in its micropylar end. Such features are common to the family as a whole. Evidenced for the first time in the family, the chalazal end of the ovule differentiates into a hypostase closely associated to the antipodal cyst. These overall features of L. fluitalls point out previous misinterpretations on some of its embryological aspects, especially those concerning the only report of simultaneous microsporogenesis and proliferation of the antipodal cells. Furthermore, the results presented here allow us to reinforce the uniformity of the embryological aspects within the Eriocaulaceae, strengthening the cystic arrangement of the antipodal cells as a potential autapomorphy of the family within the other Poales (commelinids). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: antipodal cyst; commelinids; microsporogenesis; pollen grain; seed operculum